Pioneeripataljoni üleajateenijate kogu [Engineer battalion’s non-commissioned officers’ assembly] - Lõhmus, Leho (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2012)
Non-commissioned officers belonging to Estonian army engineer battalion were assembled around a body first formed in 1925. The organization was set up for the purpose of fostering among its members an authentic esprit de corps through participation in common leisurely activities as well as organizing various educational and practical-shooting related events. Membership in the fledgling organization was made mandatory for all non-commissioned officers serving in the engineer battalion. The assembly was administered by a board of four members who respectively held the positions of a chairman, vice-chairman, secretary and treasurer. (Longer version of the current abstract is included in the article, starting from p 325.)